The expression of cyclic adenosine monophosphate responsive element modulator in rat sertoli cells following seminal extract administration - Muslim Akmal; Tongku Nizwan Siregar; Sri Wahyuni; Hamny; Mustafa Kamal Nasution; Wiwik Indriati; Budianto Panjaitan; Dwinna Aliza (Veterinary World, 2016)
Aim: This study aims to determine the effect of seminal vesicle extract on cyclic adenosine monophosphate responsive element modulator (CREM) expression in rat Sertoli cells. Materials and Methods: This study examined the expression of CREM on 20 male rats (Rattus norvegicus) at 4 months of age, weighing 250-300 g. The rats were divided into four groups: K0, KP1, KP2, and KP3. K0 group was injected with 0.2 ml normal saline; KP1 was injected with 25 mg cloprostenol (Prostavet C, Virbac S. A); KP2 and KP3 were injected with 0.2 and 0.4 ml seminal vesicle extract, respectively. The treatments were conducted 5 times within 12-day interval. At the end of the study, the rats were euthanized by cervical dislocation; then, the testicles were necropsied and processed for histology observation using immunohistochemistry staining. Results: CREM expression in rat Sertoli cells was not altered by the administration of either 0.2 or 0.4 ml seminal vesicle extract. Conclusion: The administration of seminal vesicle extract is unable to increase CREM expression in rat Sertoli cells.